Bridging the Gap: The Importance of TUBA1A α-Tubulin in Forming Midline Commissures - Buscaglia, Georgia; Northington, Kyle R.; Aiken, Jayne; Hoff, Katelyn J.; Bates, Emily A. (Frontiers in Cell and Developmental Biology, 2022)
Developing neurons undergo dramatic morphological changes to appropriately migrate and extend axons to make synaptic connections. The microtubule cytoskeleton, made of /-tubulin dimers, drives neurite outgrowth, promotes neuronal growth cone responses, and facilitates intracellular transport of critical cargoes during neurodevelopment. TUBA1A constitutes the majority of -tubulin in the developing brain and mutations to TUBA1A in humans cause severe brain malformations accompanied by varying neurological defects, collectively termed tubulinopathies. Studies of TUBA1A function in mammalian cells have been limited by the presence of multiple genes encoding highly similar tubulin proteins, which leads to α-tubulin antibody promiscuity and makes genetic manipulation challenging. Here, we test mutant tubulin levels and assembly activity and analyze the impact of TUBA1A reduction on growth cone composition, neurite extension, and commissural axon architecture during brain development. We present a novel tagging method for studying and manipulating TUBA1A in cells without impairing tubulin function. Using this tool, we show that a TUBA1A loss-of-function mutation TUBA1AN102D (TUBA1AND), reduces TUBA1A protein levels and prevents incorporation of TUBA1A into microtubule polymers. Reduced Tuba1a -tubulin in heterozygous Tuba1aND/+ mice leads to grossly normal brain formation except a significant impact on axon extension and impaired formation of forebrain commissures. Neurons with reduced Tuba1a as a result of the Tuba1aND mutation exhibit slower neuron outgrowth compared to controls. Neurons deficient in Tuba1a failed to localize microtubule associated protein-1b (Map1b) to the developing growth cone, likely impacting stabilization of microtubules. Overall, we show that reduced Tuba1a is sufficient to support neuronal migration and cortex development but not commissure formation, and provide mechanistic insight as to how TUBA1A tunes microtubule function to support neurodevelopment.